La dentición como impacto social - Ossa-S., Jorge Alberto (Revista Facultad de Odontología Universidad de Antioquia, 2016)
The importance of dentition from a social, labor and academic stand point of view is very significative. In our country doesn’t exist studies which evaluate the social impact thata good dentition has, anydeformityoftheface, including the dentition could handicap a subject from his social role. The objective of this study is to demostrate that the dentition has a great social, labor and academic importance. A working sheet was given to 200 subjects from Medellin, of both sexes, with ages ranging from 14-70 years and from any socioeconomic and intellectual status. In this working sheet they had to fill some questions regarding the importance to them of some parts of the face. The average age of the subjects was 30.1 years, 34% were males and 66% females. The answers in the worksheet revealed that the dentition is very important socially, academically and laborally. The spot of the face which is more important to the subjects are the teeth, regardless of ago, sex, occupation or socioeconomk status. The study reflects to us the great interest for the boa utiness and the self-image that people have of themselves especially of the dentition, so they could have a social active life.